Does masting scale with plant size? High reproductive variability and low synchrony in small and unproductive individuals. (24th June 2020) - Bogdziewicz, Michał; Szymkowiak, Jakub; Calama, Rafael; Crone, Elizabeth E; Espelta, Josep M; Lesica, Peter; Marino, Shealyn; Steele, Michael A; Tenhumberg, Brigitte; Tyre, Andrew; Żywiec, Magdalena; Kelly, Dave
Abstract: Background and Aims: In a range of plant species, the distribution of individual mean fecundity is skewed and dominated by a few highly fecund individuals. Larger plants produce greater seed crops, but the exact nature of the relationship between size and reproductive patterns is poorly understood. This is especially clear in plants that reproduce by exhibiting synchronized quasi-periodic variation in fruit production, a process called masting. Methods: We investigated covariation of plant size and fecundity with individual-plant-level masting patterns and seed predation in 12 mast-seeding species: Pinus pinea, Astragalus scaphoides, Sorbus aucuparia, Quercus ilex, Q. humilis, Q. rubra, Q. alba, Q. montana, Chionochloa pallens, C. macra, Celmisia lyallii and Phormium tenax . Key Results: Fecundity was non-linearly related to masting patterns. Small and unproductive plants frequently failed to produce any seeds, which elevated their annual variation and decreased synchrony. Above a low fecundity threshold, plants had similar variability and synchrony, regardless of their size and productivity. Conclusions: Our study shows that within-species variation in masting patterns is correlated with variation in fecundity, which in turn is related to plant size. Low synchrony of low-fertility plants shows that the failure years were idiosyncratic to each small plant, which in turn implies that the small plants fail to reproduce because of plant-specific factors (e.g. internal resource limits). Thus, the behaviour of these sub-producers is apparently the result of trade-offs in resource allocation and environmental limits with which the small plants cannot cope. Plant size and especially fecundity and propensity for mast failure years play a major role in determining the variability and synchrony of reproduction in plants.